PANCASILA DALAM BINGKAI KERUKUNAN BERAGAMA - Syahrul Kirom (Sekretariat Badan Litbang dan Diklat Kementerian Agama RI, 2017)
This article looks into explaining the social-religion conflict in Indonesia. The way to overcome the such conflict is to retake the pride of nationality and citizenship through Pancasila values as the philosophy of life. In other words, internalization of those values to the adherents of religion should be urgently done. So, when it happened, the adherents of religions are hopefully expected to engender the inclusive, tolerance and wise behaviors. It finally will rearrange the harmony of religions in Indonesia. KEYWORD:Pancasila, Harmony, conflict, values, religion, dialogue.